The Role of Teachers in Implementing the Problem Based Learning Model Comic Education in Reading of Elementary School Students - Mita Ernawati; Retno Winarni; Peduk Rintayati (Eduvest - Journal of Universal Studies, 2026)
This study addresses the persistent issue of low reading comprehension among elementary school students, which remains a critical challenge in achieving effective literacy learning. In many classrooms, reading instruction is still dominated by teacher-cantered approaches, resulting in limited student engagement and superficial understanding of texts. To overcome this problem, innovative learning strategies that integrate interactive models and engaging media are needed. This research aims to examine the implementation of the Problem-Based Learning (PBL) model assisted by educational comic media and its impact on students’ reading comprehension. This study employed a descriptive qualitative approach supported by simple quantitative data. The subjects were 26 fourth-grade students of an elementary school. Data were collected through observation, reading comprehension tests, and documentation. The implementation followed PBL stages, including problem presentation, group discussion, exploration, and reflection, using educational comics as learning media. The results indicate that the integration of PBL and educational comics significantly improved students’ reading comprehension and engagement. The percentage of students achieving the minimum competency standard increased from 65% in the pre-implementation phase to 84% after the intervention. Students demonstrated better ability to identify characters, interpret text, analyze content, and draw conclusions. In conclusion, the PBL model assisted by educational comic media is effective in enhancing reading comprehension and fostering active learning. This approach can serve as an alternative strategy to improve literacy instruction in elementary schools.